A comprehensive study on a novel concentric cylindrical thermoelectric power generation system - Huang, Kuo; Li, Bo; Yan, Yuying; Li, Yong; Twaha, Ssennoga; Zhu, Jie (Elsevier, 2017)
This paper presents the novel designs of a concentric cylindrical thermoelectric generator (CCTEG) and an annular thermoelectric module (ATEM). The simulations are carried out to compare the performance of ATEM and the conventional square-shaped thermoelectric module (STEM). The heat pipe technology is introduced into the heat sink system in order to enhance the heat transfer in the radial direction of exhaust gas flow. A new index termed as the heat transfer filling factor ff has been introduced which quantities the level of space utilisation for thermoelectric modules (TEMs). The correlation between the coolant flow rate and TEM performance is also carried out. Experimental work is also carried out to demonstrate the viability of using the heat pipes for heat transfer enhancement as well proving the viability of the design. The simulations indicate that the open circuit electric potential of the ATEM is 17% more than that of the STEM. The experimental results show that the CCTEG system performs well under various conditions. This results also demonstrate that the concept of adding heat pipes to the heat sink system is a practical solution to achieve higher thermoelectric generator (TEG) performance while maintaining the compactness of the TEG system. A heat transfer filling factor of 0.655 is achieved for the CCTEG system which is higher compared to the existing TEG systems. Moreover, a higher coolant flow rate contributes to obtaining a better performance of the TEG system. It is important to note that the introduced index can give guidance for further optimisation design of TEG systems.